Ethylene Biosynthesis and Accumulation under Drained and Submerged Conditions (A Comparative Study of Two Rumex Species). - Banga, M. (1996)
A model is presented of the regulation of ethylene biosynthesis in relation to submergence and flooding resistance. It is based on time-course measurements of ethylene production, ethylene accumulation, and concentrations of free and conjugated 1-aminocyclo-propane-1-carboxylic acid (ACC) in submerged and drained flooding-resistant Rumex palustris Sm. and flooding-sensitive Rumex acetosella L. plants. From these data, in vivo reaction rates of the final steps in the ethylene biosynthetic pathway were calculated. According to our model, submergence stimulates ACC formation and inhibits conversion of ACC to ethylene in both Rumex species, and as a result, ACC accumulates. This may explain the stimulated ACC conjugation observed in submerged plants. Although submergence inhibited ethylene production, physical entrapment increased endogenous ethylene concentrations in both flooding-resistant R. palustris and flooding-sensitive R. acetosella plants. However, R. palustris plants controlled their internal ethylene levels in the long term by a negative regulation of ACC synthase induced by ethylene. In flooding-sensitive R. acetosella plants, absence of negative regulation increased internal ethylene levels to more than 20 [mu]L L-1 after 6 d of submergence. This may accelerate the process of senescence and contribute to their low level of flooding resistance.